2019
DOI: 10.3389/fnmol.2019.00181
|View full text |Cite
|
Sign up to set email alerts
|

Can We Use 2,3,5-Triphenyltetrazolium Chloride-Stained Brain Slices for Other Purposes? The Application of Western Blotting

Abstract: 2,3,5-Triphenyltetrazolium chloride (TTC) staining is a commonly used method to determine the volume of the cerebral infarction in experimental stroke models. The TTC staining protocol is considered to interfere with downstream analyses, and it is unclear whether TTC-stained brain samples can be used for biochemistry analyses. However, there is evidence indicating that, with proper optimization and handling, TTC-stained brains may remain viable for protein analyses. In the present study, we aimed to rigorously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 43 publications
1
23
0
Order By: Relevance
“…Protein extraction and Western blotting were performed as previously described [ 63 , 64 ]. Hippocampus samples were sonicated in 300 μL lysis buffer (50 mM tris(hydroxymethyl)aminomethane buffer pH 7.4 containing 80 μM ammoniummolybdate, 5 mM β -glycerolphosphate, 1 mM dithiothreitol, 1 mM ethylenediaminetetraacetic acid, 1% sodium dodecyl sulfate, 1 mM sodium pyrophosphate, 1 mM sodium vanadate, 1 cOmplete™ protease inhibitor cocktail tablet, and 1 PhosSTOP™ phosphatase inhibitor cocktail tablet) and centrifuged at 14000 g for 20 min at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Protein extraction and Western blotting were performed as previously described [ 63 , 64 ]. Hippocampus samples were sonicated in 300 μL lysis buffer (50 mM tris(hydroxymethyl)aminomethane buffer pH 7.4 containing 80 μM ammoniummolybdate, 5 mM β -glycerolphosphate, 1 mM dithiothreitol, 1 mM ethylenediaminetetraacetic acid, 1% sodium dodecyl sulfate, 1 mM sodium pyrophosphate, 1 mM sodium vanadate, 1 cOmplete™ protease inhibitor cocktail tablet, and 1 PhosSTOP™ phosphatase inhibitor cocktail tablet) and centrifuged at 14000 g for 20 min at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Photothrombotic occlusion was performed as described previously with minor modifications 19,25 . Briefly, mice were anaesthetized by 2% isoflurane during the surgical procedure on a temperature-regulated (37 °C ± 1) stereotaxic frame.…”
Section: Photothrombotic Occlusionmentioning
confidence: 99%
“…Brain tissues were used for Western blot analysis after first being stained with TTC and imaged. Previous studies demonstrated that TTC-stained brain tissues could be used for quantitative gene and protein expression analyses using real-time polymerase chain reaction (RT-PCR) and Western blot in models of ischemic stroke including in the HI rat model without altering the expression of proteins [ 52 54 ]. After TTC staining, slices were imaged and recorded at 48 h post-HI, and the brain slices were instantly divided into the ipsilateral and contralateral cerebrums, snap frozen in liquid nitrogen, and then stored in a − 80 °C freezer for Western blot.…”
Section: Methodsmentioning
confidence: 99%